Factors Affecting to Performing and Nonperforming Borrower’s Loan Repayment Ability - Dedunu, H.H.; Fernando, A.A.J. (My University, 2017)
Abstract : The research examined factors affecting performing and non performing borrower’s repayment ability of Regional Development Bank in North Central Province. This study was done collecting data from both performing and non performing borrowers of Regional Development Bank in Medirigiriya area. The dependent variable of the study was loan repayment ability and the independent variables were information about borrower’s income, loan amount, borrower’s background, accessibility of getting loan and information about guarantee. The collected data analyzed using descriptive statistics, correlation and regression analysis. According to regression result of performing holders, it was found that information about guarantee has significantly impact on borrower’s loan repayment ability. On the other hand, the regression result of non performing holders indicated that there are statically significant impact of background investigation and information about guarantee on loan repayment ability. Key Words: Performing borrowers, Non- Performing Borrowers, Loan Repayment